Peran Pelatihan Dan Peningkatan Keterampilan Tenaga Kesehatan Dalam Penanganan Difteri Di Jawa Timur Pada Tahun 2024 - Mustikasari, Rahma Ira; Husada, Dominicus; Kartina, Leny; Basuki, Parwati Setiono; Puspitasari, Dwiyanti; Ismoedijanto, Ismoedijanto; Hilwana, Lutifta; Haq, Arini (Universitas Mataram, 2025)
Diphtheria, caused by Corynebacterium diphtheriae, is a significant public health threat, particularly in areas with low immunization coverage. Despite national immunization programs, sporadic outbreaks continue to occur, especially in East Java, which reported the highest number of cases in 2021. The disease is transmitted through respiratory droplets and can lead to severe complications if not diagnosed and treated promptly. Diphtheria mortality can be reduced with appropriate treatment, along with good immunization status. Diagnosis can be made both clinically and through laboratory tests, including culturing the diphtheria bacteria from swabs of affected tissues. This community service program aimed to enhance the capacity of healthcare workers in East Java, specifically in Sampang Regency, to manage diphtheria through training that included both theoretical and practical components. The training methods used included pre- and post-tests to assess knowledge, mini lectures on epidemiology, clinical symptoms, diphtheria vaccination, and management, along with case simulations to improve participants' practical skills. The program was attended by 42 participants from various healthcare professions, including doctors, nurses, health analysts, and surveillance officers The evaluation demonstrated a significant improvement in participants' knowledge after the training. This program contributed meaningfully to enhancing preparedness among local healthcare providers and is expected to support more robust early detection and response systems for diphtheria outbreaks in the future.